Comparison of four endoluminal radiofrequency ablation devices and four power generators in an ex vivo bovine liver model - Rheinheimer, Stephan; Jacobsen, Anna; Mayer, Philipp; Kauczor, Hans-Ulrich; Mahnken, Andreas H. (World Academy of Sciences journal, 2021)
The aim of the present study was to investigate the ex vivo results of four different endoluminal bipolar radiofrequency ablation (RFA) probes at different energy settings and using four different power generators. Ex vivo RFA was performed on bovine liver using four different bipolar RFA probes: i) Habib™ EndoHPB (EMcision); ii) Habib™ VesOpen (EMcision); iii) Celon ProCurve micro 300‑C09 (Olympus Corporation); and iv) Celon ProCurve 1200 S15 (Olympus Corporation). The following generators were also used: Erbe Vio 300D, KLS Martin Maxium, Olympus CelonPOWER and Boston RF3000. Overall, 430 ablations were carried out. The results revealed significant differences in the size of the achieved lesions and the duration of ablation (P<0.05) between the four different ablation devices. The maximum lesion diameters achieved with the devises were as follows: HabibTM EndoHPB, 13 watts (W; mean ± standard deviation, 10.3±1.8 mm); Habib™ VesOpen, 12 W (11.3±0.6); Celon ProCurve micro, 2 W (7.9±2.2); and Celon ProCurve 1200, 10 W (9.2±1.1). The maximum lesion diameters induced by the various generators differed significantly. On the whole, the present study demonstrates that lesion size and ideal power settings vary between different endoluminal ablation devices and generators. The combination of the probe and generator should not be varied in clinical practice to ensure reliable results.
Gesehen am 23.05.2023